Menopause and Haematological Changes: a case control study (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Menopause is the natural cessation or stopping of a woman’s menstrual cycle and marks the end of  fertility. Ovarian function declines can lead to undesirable alterations in metabolism, vascular endothelium  function, fibrinolytic and coagulative properties of blood. Menopause may enhance risk for ischemic heart disease  in women due to such altered properties of blood and vascular function.  Aims and Objectives: To compare some haematological values in pre- and post-menopausal women to know the  risk of vascular and ischemic heart disease in postmenopausal women.  Materials and Methods: Blood samples were drawn in 50 women who have attained menopause and have weight  of 55–60 kg and height of 150–160 cm and 50 control subjects who were disease-free women aged 35–40 years  with matching weight and height. These women had natural menopause and were not subjected to any hormonal  or surgical intervention. The vital parameters were recorded, and general examination was done. Results: There was a statistically significant increase in hematocrit, and there was no statistically significant  change in platelet count, activated partial thromboplastin time (APTT), and prothrombin time (PT).  Conclusion: A higher viscosity of blood can enhance the risk of coronary artery disease by elevating platelet  aggregability and adhesiveness to sub-endothelium. However, the above effect may partially be offset by  unchanged APTT and PT.
Keywords: Menopause; Haematological; Coronary Artery Disease; Estrogen; Hematocrit; Platelet; Subendothelium